(untitled) (Journal of the College of Basic Education, 2026)
The current study aims to identify the effectiveness of the strategy (Collect – Summarize – Build Your Knowledge) in the academic achievement of fifth-grade female students in the subject of Science. The researchers adopted the quasi-experimental method with two equivalent groups. To achieve the objective of the study, a random sample consisting of (62) students from (Zulfiqar Primary School for Girls), affiliated with the General Directorate of Education in Baghdad Governorate/Al-Rusafa 2, was selected. They were divided into an experimental group (30) students and a control group (32) students. The equivalence between the students of the two study groups was carried out according to the following variables: (chronological age calculated in months, parents’ academic achievement, prior achievement in science, prior knowledge test, and intelligence test) for the first semester of the academic year (2025-2026). The educational material consisted of the first six chapters of the fifth-grade science textbook, which included (152) behavioral objectives distributed according to the six levels in Bloom’s taxonomy. Based on this, the researchers prepared two teaching plan models for each group. An achievement test consisting of (30) multiple-choice items was prepared, and its validity and reliability were verified. The statistical methods were employed.